1992
DOI: 10.1097/00006842-199207000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular differentiation of emotions.

Abstract: This study examined the cardiovascular mechanisms governing differential blood pressure changes during the emotions of joy, sadness, fear, and anger. Heart rate, blood pressure, stroke volume, peripheral vascular resistance, cardiac output, and indices of myocardial contractility were measured during fear, anger, joy, sadness, physical action, and neutral imagery conditions in 27 right-handed male volunteers screened for imagery ability, alexithymia, anxiety, and depression. Anger imagery, rather than fear, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
168
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(182 citation statements)
references
References 23 publications
10
168
1
Order By: Relevance
“…While this study and others (6) suggest that the observed increases in regional brain activity cannot be completely attributed to aspects of the tasks that are unrelated to emotion, additional studies are needed to consider this issue further. Additional studies are also needed to determine the extent to which modality-specific sensory association areas and anterior temporal lobe structures participate in the emotional response to other kinds of exteroceptive sensory stimuli, the extent to which anterior temporal lobe structures participate in internally generated fear (an emotion that is distinguished from the target emotions elicited in this study by consistent increases in autonomic activity [42,43]), and the extent to which our findings can be generalized to males, different age groups, people who are not right-handed, individuals who vary in their ability to have intense emotions, and those who are not instructed to feel the target emotion.…”
Section: Resultsmentioning
confidence: 99%
“…While this study and others (6) suggest that the observed increases in regional brain activity cannot be completely attributed to aspects of the tasks that are unrelated to emotion, additional studies are needed to consider this issue further. Additional studies are also needed to determine the extent to which modality-specific sensory association areas and anterior temporal lobe structures participate in the emotional response to other kinds of exteroceptive sensory stimuli, the extent to which anterior temporal lobe structures participate in internally generated fear (an emotion that is distinguished from the target emotions elicited in this study by consistent increases in autonomic activity [42,43]), and the extent to which our findings can be generalized to males, different age groups, people who are not right-handed, individuals who vary in their ability to have intense emotions, and those who are not instructed to feel the target emotion.…”
Section: Resultsmentioning
confidence: 99%
“…Conducting these analyses requires having single data points for anger and BP to compare across people, which can mean aggregating variables (e.g., calculating a difference score between anger at baseline and after an argument). These between-person approaches have successfully been used to show that those who are provoked during a task involving active coping were those with the greatest cardiovascular activity (Bongard, Pfeiffer, al'Absi, Hodapp, & Linnenkemper, 1997), that different emotions produce distinct cardiovascular profiles (Sinha, Lovallo, & Parsons, 1992), and that coherence between responding to anger provocation was higher when comparing within systems (automatic and reflexive) versus across them (Evers et al, 2014).…”
Section: The Distinct Questions Tested By Between-person and Within-pmentioning
confidence: 99%
“…In the laboratory, various methods are used to induce specific emotional states and determine how they may be differentiated physiologically (for example, Sinha, Lovallo, & Parsons, 1992). In everyday life, however, emotional experiences and reactions are not unitary, and they vary in their duration, complexity, and intensity.…”
Section: Introductionmentioning
confidence: 99%